The profiles of immunosuppressive microenvironment in the Lauren intestinal-type gastric adenocarcinoma - Qingyuan Wang; Jia Chen; Yaohui Wang; Xiang Li; Xiaochun Ping; Jiajia Shen; Sheng Yang; Lizong Shen (Cancer Immunology, Immunotherapy)
Abstract Background Gastric adenocarcinoma (GAC), particularly the Lauren intestinal-type GAC (IGAC), leads to significant mortality in China due to the limited effectiveness of current treatments. This study aims to investigate the mechanisms of immune suppression in IGAC to identify potential targets for enhancing immunotherapy outcomes. Methods Performing an extensive collection and re-analysis of single-cell RNA sequencing (scRNA-seq) of tumor tissues and the corresponding noncancerous mucosae from 15 Chinese patients diagnosed with IGAC, we identified cell subpopulations involved in immune suppression within the tumor microenvironment (TME). We further validated our findings using spatially resolved transcriptomics (SRT), immunofluorescence (IF), and flow cytometry (FCM) on tissues from IGAC patients. Results We demonstrated that the TME of IGAC harbors CD8+ exhausted T cells (Texs) and various subtypes that mediate immunity. We identified specific subpopulations of Texs (HAVCR2 + VCAM1 +) and regulatory T cells (Tregs) (LAYN + TNFRSF4 +) contributing to immune suppression. Furthermore, TNFRSF12A + cancer-associated fibroblasts (CAFs), CTSB + macrophages, and SOD2 + monocytes were found to be involved in maintaining the immunosuppressive milieu. SRT and IF assays confirmed the presence and colocalization of these cell types within the tumor tissues, highlighting their functional interactions. FCM assays indicated that the prevalence of HAVCR2 + VCAM1 + Texs and LAYN + TNFRSF4 + Tregs in tumor tissues was positively associated with IGAC progression. Conclusions Detailed profiles of immunosuppressive cell subpopulations in IGAC provide valuable insights into the complexity and heterogeneity of immunosuppression. These findings underscore the necessity for targeted strategies that disrupt specific immunosuppressive pathways, potentially enhancing the efficacy of immunotherapeutic interventions in IGAC.